2009
DOI: 10.1111/j.1743-6109.2009.01242.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dysfunction Is Frequent in Premenopausal Women with Diabetes, Obesity, and Hypothyroidism, and Correlates with Markers of Increased Cardiovascular Risk. A Preliminary Report

Abstract: Introduction Female sexual dysfunction (FSD) is characterized by reduced sexual appetite and altered psychologic and physiologic response to sexual intercourse; it is reported to be frequent in diabetes mellitus, but no data have been reported in thyroid disorders. Aims To compare the prevalence of FSD in diabetic, in obese, and in hypothyroid women vs. healthy women, and to correlate FSD with endocrine and metabolic profiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
82
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 44 publications
(54 reference statements)
11
82
1
1
Order By: Relevance
“…In addition, the FSFI global score was negatively correlated with the known risk factors for cardiovascular disease, such as blood pressure, HbA1c, low-density lipoprotein cholesterol and TSH, whereas it was positively correlated with high-density lipoprotein cholesterol. 23 In our study, there was no difference between obese and overweight women and controls in terms of FSFI scores. As a score of p26.55 indicated FSD, 86% of obese patients and 83% of controls were considered to have sexual dysfunction, suggesting that obesity itself is not a major determining factor in sexual dysfunction in women.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In addition, the FSFI global score was negatively correlated with the known risk factors for cardiovascular disease, such as blood pressure, HbA1c, low-density lipoprotein cholesterol and TSH, whereas it was positively correlated with high-density lipoprotein cholesterol. 23 In our study, there was no difference between obese and overweight women and controls in terms of FSFI scores. As a score of p26.55 indicated FSD, 86% of obese patients and 83% of controls were considered to have sexual dysfunction, suggesting that obesity itself is not a major determining factor in sexual dysfunction in women.…”
Section: Discussionmentioning
confidence: 69%
“…13 However, weight reduction seems to improve sexual function in young obese women. [20][21][22] Veronelli et al 23 reported that obese women had a lower score in the FSFI questionnaire when compared with healthy women, and a higher FSFI score was associated with a healthier anthropometric and metabolic status. In addition, the FSFI global score was negatively correlated with the known risk factors for cardiovascular disease, such as blood pressure, HbA1c, low-density lipoprotein cholesterol and TSH, whereas it was positively correlated with high-density lipoprotein cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…The overall FSD prevalence rate in our study was approximately 54%, which is higher than that reported in younger women with type 1 diabetes (up to 35%). 12 The studies that until now addressed FSD in women with type 2 diabetes suffer most from small sample size: 13,14,16,30,31 in all these studies sample size was well below 100 diabetic patients (range 30-72 women), and all studies reported a higher prevalence of FSD in diabetic women as compared with matched nondiabetic women. In the largest study so far published, Abu Ali et al 15 evaluated 613 diabetic women and 524 nondiabetic women in Jordan, and found a prevalence of FSD of 59.6% in diabetic women 50 years of age or older as compared with 45.6% found in the age-matched nondiabetic women (Po0.05).…”
Section: Discussionmentioning
confidence: 99%
“…This difference in the quality of sexual life is due to factors inherent to age, such as poor health of both women and their partners, which negatively influence sexuality. [6][7][8][9][10][11] Specific aspects of men's health and their role in society influence their life expectancy, causing women to often lose their partners faster than expected, which negatively affects female sexual function. 6,9 The aging process is associated with diminished libido, possibly resulting from physiological changes.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown the negative effects of aging on the quality of women's sexual life, with a growing prevalence of sexual dysfunction in aging women. [6][7][8][9][10][11] Only a small proportion of older women are sexually active, and only 10 to 20% of them have frequent sexual intercourse after their 60s. 12 Considering the lack of self-administrated, userfriendly and effective national questionnaires capable of evaluating various facets of female sexual function in any age group and all phases of the sexual cycle, the Female Sexual Quotient Questionnaire (FSQ) was developed as an instrument to evaluate the quality of sexual life of Brazilian women.…”
Section: Introductionmentioning
confidence: 99%